Tanggungjawab Hukum Notaris Terhadap Pembatalan Akte Perjanjian Pengikatan Jual Beli Hak Guna Bangunan - Eka Rachma Putri; Fauzi Yusuf Hasibuan; Sulhan S (Postgraduate of Jayabaya University, 2019)
The problem of this research is how the legal responsibility of notary on the cancellation of the agreement on the binding of sale and purchase of building rights and how the legal protection of the holder of the abandoned purchase agreement of Hak Guna Bangunan. In order to conduct this research, research method used by writer is normative juridical research method supported by empirical data, using normative juridical approach because the target of this research is law (norm). The result of the research that the legal force of the deed of binding agreement of sale and purchase of land rights made by Notary in the execution of the Deed of Sale is very strong, because the deed is a notary certificate that is authentic deed, the giving of irrevocable power in sale binding agreement Purchase is not included in the absolute power prohibited by the Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition of the Use of Absolute Power as the Transfer of Building Use Rights, and Protection of the law against the fulfillment of the rights of the parties if either party default in the sale and purchase agreement Depends heavily on the strength of the contract of sale and purchase that is made, that is, if it is made under a deed under the hand, its protection in accordance with the protection of the deed under the hand.